EFFECT OF POSITION PROMOTION AND EMPLOYEE COMPETENCY ON EMPLOYEE PERFORMANCE THROUGH WORK MOTIVATION - Loren Dina Dasilfa; Suwignyo Widagdo; Yuniorita Indah Handayani (MBA - Journal of Management and Business Aplication, 2022)
Human resources (HR) is one of the main driving forces that are important fororganizations/agencies because human resources are the implementers of every activity. For thisreason, a "fit" Human Resource Management (HRM) is needed in order to achieve highperformance. With a business strategy and appropriate HR practices (fit/match) it will result inorganizational performance that can achieve program realization targets. The purpose of thisstudy was to determine the direct or indirect effect of promotion and employee competence onemployee performance through work motivation as an intervening variable on the employees ofthe Bondowoso Regency Government. The total population of this study was 601 with a sampleof 120 respondents. The sampling technique used was purposive sampling. The analyticaltechnique used is path analysis using SPSS 22.0. The results of data analysis show that thevariable of job promotion has a significant effect on work motivation, employee competence hasa significant effect on work motivation, job promotion has a significant effect on employeeperformance, employee competence has a significant effect on employee performance, workmotivation has a significant effect on employee performance. Indirectly, promotion andemployee competence have a significant effect on employee performance through employeeperformance with the value of the indirect effect being greater than the direct effect. The resultsof this study can be used as an evaluation of the Regional Government of Bondowoso Regencyin terms of providing promotions to employees by considering their competence andperformance.